NEGOTIATED URBAN SPACE AT MANGGARAI STATION JAKARTA: THE APPROPRIATION OF SPACE BY BAJAJ DRIVERS - Yulia Nurliani Lukito; Rumishatul Ulya (Dimensi: Journal of Architecture and Built Environment, 2018)
This paper aims to investigate the negotiation between the “formal” and the “informal” urban space in Jakarta through the examination of use of space of marginalized transportation of bajaj – a three-wheeled public transportation. Bajaj drivers continuously and creatively create their use of space and territory as the result of the limitation of space. Creativity in using space emerges as a way to get available space and this activity results in the appropriation of urban space. The basis of such appropriation is how to survive in urban space and such condition is characterized by negotiation, flexibility and adaptability. In high-density Jakarta city, it is necessary for bajaj drivers – who have only limited possibility in using strategic urban space – to use both the formal and the informal to sustain the city at large. An analysis of how bajaj drivers negotiated urban spaces around Manggarai Station reveals the appropriation of urban space that relies on temporality, tactics and negotiation of rules of access among users. In this paper, we analyze how urban informality as an ‘organizing logic’ results in a specific mode of the production of space. The analysis of negotiations of space around Manggarai Station is intended to contribute to an understanding of how informal and negotiated spaces, which shape everyday life in the city, are inseparable parts of formal and designed spaces in the city of Jakarta.